The Learning Approach To Writing Indonesian In The Middle School: Ethnographic Study of Indonesian Language Learning at SMAN - Reni Nur Eriyani; Emzir Emzir; Fathiaty Murtadho (Indonesian Journal of Learning Education and Counseling, 2020)
The purpose of this study in general is to gain a deep understanding of the learning approach to writing at SMAN 1 Cipanas. This study uses a qualitative approach with ethnographic methods based on the consideration that this study intends to examine and examine in more depth the Indonesian language learning approach. The results of the study illustrate that the approaches used at SMAN 1 Cipanas are communicative, scientific, collaborative, text genre, and student-centered approaches. With the approach used by the teacher, students become more active in the learning process, learning is more meaningful and efficient and fosters student interest.